Spinning straw into milk: Can a 95% byproduct diet support milk production? - Hulett, M.; Ylioja, C. M.; Wickersham, T. A.; Bradford, Barry J. (My University, 2016)
Agriculture is challenged with the need to support increasing human populations without additional land. One way the livestock industry has addressed this is by using human inedible feedstuffs, including industrial byproducts. Many dairy and feedlot diets incorporate 20–40% byproduct feeds, but few studies have evaluated responses of lactating dairy cattle to diets composed almost entirely of byproducts. Our objective was to evaluate such a diet in comparison to a more traditional lactation diet. The control diet was primarily composed of alfalfa hay, corn silage, corn gluten feed, and corn grain. The by-product diet included wheat straw, corn hominy, post-extraction algae residue, and corn gluten feed; in addition, 4% molasses was included to improve palatability. The control and by-product diets had similar concentrations of DM (50.6%) and CP (17.2%), whereas the byproduct diet included slightly more NDF (32.9 vs. 30.5%) and less fat (4.7 vs. 5.2%). Twelve Holstein cows (154 ± 20 DIM) were blocked by parity (primiparous vs. multiparous) and randomly assigned to treatment sequence in a crossover design. Diets were fed for 20 d, with data and sample collections over the final 3 d of each period. One cow was removed from byproduct diet after refusing to consume it, and data from this period were not included in the analysis. Data were analyzed with mixed models to assess fixed effects of diet, parity, and their interaction as well as the random effects of cow and period, and significance was declared at P < 0.05. The one selective cow notwithstanding, DMI was not affected by treatment. Milk yield of multiparous cows was decreased by the byproduct diet (38.7 vs. 42.3 ± 2.2 kg/d) but there was no treatment effect in primiparous cows (39.3 vs. 39.4 ± 2.2 kg/d). The byproduct diet decreased milk fat content (3.3 vs. 3.6 ± 0.12%) and tended to decrease protein content (2.94 vs. 2.99 ± 0.05%), and energy-corrected milk yield was decreased by 5.4 kg/d in multiparous cows and 1.5 kg/d in primiparous cows. No effects on BW or BCS were detected. Despite negative productivity responses, calculated recoveries of human-edible protein and energy in the diet were increased by approximately 50% with the byproduct diet, changing from a net loss to a net gain in human-edible energy and protein. A diet composed of 95% byproduct feeds supported milk yield of 39 kg/d and increased the efficiency of production from a human-edible input perspective.
Citation: Hulett, M., Ylioja, C. M., Wickersham, T. A., & Bradford, B. J. (2016). Spinning straw into milk: Can a 95% byproduct diet support milk production? Journal of Animal Science, 94, 187-187. doi:10.2527/msasas2016-400
Keywords: Sustainability; Byproduct Feeds; Lactation; Dairy; Agriculture